SACRED GROVE (KAVU): ANCESTRAL LAND OF LANDLESS AGRICULTURAL LABOURERS IN KERALA, INDIA - YASUSHI UCHIYAMADA (LONDON SCHOOL OF ECONOMICS AND POLITICAL SCIENCE, UNIVERSITY OF LONDON, 1995)
The thesis focuses on land reforms and ghosts of Untouchables in Kerala, India. More specifically, it is about a conflict between two sets of logic and praxis: land reform on the one hand, and people-land relatedness as it is performed and disclosed by Untouchables, on the other. The former are people-government-land relations and the latter is people-ancestor-land relatedness. The thesis consists of two sections and a concluding chapter. In Part I, I juxtapose a coherent dominant history and fragmented parallel histories to shed light on artifactuality of "landlessness". The dominant history is about how agrestic slaves were freed (from land) in the mid-19th century and then became landowners, as a result of the radical land reforms. According to the parallel histories, by contrast, Untouchables have been dislocated from their ancestral lands since the last century and this process culminated in the land reforms. In Part II, I describe the ways in which people-ancestor-land connectedness is disclosed and reproduced by Untouchables through performing ancestor worship in kaavu ("sacred grove"). In one case history, I describe how untouchable squatters, who were dislocated from their ancestral land in the mid-1960s, invoke their ancestor spirits (who are believed to be haunting in their ancestral land) in order to regain their ancestral land from a new outsider landowner, who acquired the land during the land reform. In the concluding chapter, I discuss resistance. Cults of the dead performed by Untouchables disclose and reproduce people-ancestor-land connectedness and provide explanations of why misfortunes strike landowners, who are not connected to the land through ancestors, but through title deeds. When the "landless agricultural labourers", who lost their "ancestral lands", perform cults of the dead, the message of people- ancestor-land connectedness and consubstantiality spills over into the political field and turns into resistance.